Pengembangan Instrumen Assesmen Berfikir Kreatif Pada Mata Pelajaran PKN Terintegrasi Nilai-Nilai Pendidikan Karakter - Leli Suryani Rambe, Safrida Napitupulu (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2021)
This study aims to produce an assessment instrument for creative creative thinking in Civics subjects integrated with character education values, Knowing the feasibility of an assessment instrument for creative thinking, Knowing the quality of an assessment instrument for creative thinking in Civics subjects integrated with character education values ??for grade IV SD. Creative thinking ability There is no assessment instrument to assess students' creative thinking. This is because students are not trained in working on questions that measure creative thinking skills and assessment instruments specifically designed to train creative thinking skills are not yet available, so the development of creative thinking assessment instruments is needed. This type of research is Research And Development (R&D). using the Borg and Gall development steps adopted by Sugiono. The research steps used by researchers only reached the seventh stage, namely: potential and problems, data collection, product design, design validation, design revision, product testing and product revision. This research was carried out at SDN 066668 Medan Johor on August 26, 2021. Based on product validation by three expert lecturers and 1 elementary school educator, an assessment instrument for creative thinking was produced in Civics subjects integrated with character education values ??for grade IV SD which was feasible to use. The percentage of eligibility for each validator is 84.61% feasibility assessment, 88.45% material feasibility and 86.10% language eligibility.